PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN MEMBELI DI COUNTER HANDPHONE PLAZA AMBARUKMO - Diana Sari Wijayanti, Irine (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2024)
This research aims to find out whether there is an influence of the Promotion Mix on the Purchase Decision at the Plaza Ambarukmo Yogyakarta Mobile Counter and to find out which Promotion Mix factors have the greatest influence on the Purchase Decision at the Plaza Ambarukmo Yogyakarta Mobile Counter. The results of the simultaneous hypothesis test stated that Ho was rejected, meaning that the variables Personal Selling, Advertising, Sales Promotion and Direct Marketing together had an effect on decision to buy at the Mobile Counter Plaza Ambarukmo Yogyakarta because the F-count (3,201) is greater than the F-table (2,467). The results of the dominant analysis show that the Advertising variable has the most dominant influence on the purchasing decision variable at the Mobile Counter Plaza Ambarukmo Yogyakarta because the results of the analysis of this variable have the largest t-value (2.488). Based on the results of the analysis of the coefficient of determination, it states that the magnitude of influence exerted by the variables Personal Selling, Advertising (Advertising) Sales Promotion Direct Marketing on purchasing decisions in Plaza Ambarukmo Yogyakarta Mobile Counter was 11.9%.